External conflicts and Malaysia's National Security: the case of Daesh - El-Muhammady, Ahmad (Malaysian Institute of Defence and Security, 2017)
This paper attempts to explore the implications of conflicts emanated from the international, regional and the local settings to Malaysia's national security. The paper argues that the threats to Malaysia ssecurity is not a new phenomenon. Threats to Malaysia ssecurity has been a constant variable manifesting in variousforms and degree of intensity since 1940s until today. However, the intensity of conflicts taking place in the Middle East and the threats of Islamic State (IS) group or Daesh compounded with the existence of several "hotspots" of conflicts is bound to make security environments in Southeast Asia more exposed and vulnerable to terrorism threats.In turn,it is bound to affect Malaysia's national security. The situation is increasingly alarming in Malaysia, as the national police,the RoyalMalaysiaPolice (RMP) has detained more than 300 suspects since 2013, including government servant, security personnel and the youth of below forty years old. The region also witnesses the emergence of new threats landscape (NTL) posed by IS. It is characterized by the change in the nature of threats from state to non-state actor, single to multiple threats, group to lone wolf, social media to smartphone, social media as the mass recruiter, and etc. Given the nature of the threats, thepaper argues Malaysia needs to take proactive measures to prevent terrorism threatsfromgrowing inside. Five recommendations areputf orward to mitigate the threats namely, allocation of significant investment in military and security expenditure, crafting National Counterterrorism Strategy, creating Cyber Force unit attached to Ministry of Defence, countering extremist ideology initiatives and being more active asf acilitator or mediator in regional conflicts.